Tanaman Obat Aplikasi Search Engine Tanaman Obat Di Pegunungan Arfak: Medicinal Plants Search Engine Application In the Arfak Mountains - Achmad Chairuddin Agrifandi; Christian Dwi Suhendra; Lion Ferdinand Marini (JISTECH: Journal of Information Science and Technology, 2023)
The Faculty of Forestry, University of Papua has a lecturer named Dr. Ir. Budi Susilo Budihusodo, MP has data on medicinal plants in West Papua Province, Arfak Mountains district, with as much data as 70 medicinal plants. These medicinal plant data were researched and lab tested directly by Dr. Ir. Budi Susilo Budihusodo, MP at Mulawarman University in the city of Samarinda, East Kalimantan and at the University of Papua. These data want to be developed into a Search Engine Application so that users can search and find out the benefits and uses of medicinal plants in the Arfak Mountains District of West Papua. This Search Engine application is made web-based, using PHP, MySQL as a database, and XAMPP as a web server. This Search Engine application is designed with a very simple flow and interface design so that it can be easily used, with the Medicinal Plants Search Engine application users are able to get information about the medicinal plants they are looking for.